The Ambiguous Construction of a Modern Melancholic Self: Evanthia Kairi’s Correspondence, 1814–1866 - Zei, Eleftheria (The Historical Review/La Revue Historique, 2022)
Evanthia Kairi was an author and literary woman who lived during the first half of the nineteenth century (1799–1868). She produced few literary works but left a rich correspondence covering the period from 1814 to 1866; most of her letters are addressed to her elder brother, the priest, philosopher and revolutionary Theophilos Kairis. Generally based on a nineteenth-century perception of melancholy as a romantic, dark, often pathological, condition, that related particularly to women, contemporary historiography considers her as an altogether idiosyncratic, solitary and melancholic intellectual. This article ventures to propose an anatomy of Kairi’s melancholic discourse in the light of a modern “active sensibility”, that is, as a procedure of construction and deconstruction of a modern virtuous self through different life narratives: her moral shaping and education in modern virtues, her strict and complex pattern of social and affective exchanges within the family and her language of solitariness.